KEEFEKTIFAN METODE PEMBELAJARAN NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MEMBACA MAHASISWA PADA MATA KULIAH DOKKAI 3 - Misra Lusi; Hadriana Hadriana; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: the purpose of this study is to describe the effectiveness of Number Head Together Method (NHT) to improve student’s reading comprehension skill in dokkai 3 course. This study is a weak experimental research with one group pretest posttest design. The object of this research was 22 students class A of 2016/2017 of Japanese study program faculty of teachers training and education at the university of Riau. The sampling technique that used was purposive sampling technique. The type of data collection technique in this research was giving a test. The test consisted two type of tests, namely pretest and posttest. Pretest and posttest was conducted by giving the student a reading comprehension test. The result of pretest and posttest was processed by SPPS of software 23 IBM version For windows. Based on the analysis, the student’s pretest average score was 82. It means there was an increase of student’s pretest result to result. Thus, it can be concluded that number head together (NHT) method is effective to improve student’s reading comprehension ability in Dokkai 3 course of Japanese study program faculty of teachers training and education at the university of Riau.Key Words: Dokkai, Number Head Together (NHT), Reading Comprehension.